1990
DOI: 10.1172/jci114548
|View full text |Cite
|
Sign up to set email alerts
|

A major crossreactive idiotype associated with human antibodies to the Haemophilus influenzae b polysaccharide. Expression in relation to age and immunoglobulin G subclass.

Abstract: IntroductionUsing idiotypic analysis, we examined the variable (V) region diversity of human antibodies specific for the capsular polysaccharide of Haemophilus influenzae b (Hib PS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…Generation of hybridoma cell lines secreting human monoclonal anti-Hib PS Ab has been previously described (2,6). Briefly, healthy volunteers were immunized with either Hib PS conjugated to diphtheria toxoid (Hib PS-D) (Connaught Laboratories, Swiftwater, PA) or Hib oligosaccharide conjugated to Corynebacterium diphtheriae CRMI9' protein (Lederle Laboratories, Wayne, NJ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generation of hybridoma cell lines secreting human monoclonal anti-Hib PS Ab has been previously described (2,6). Briefly, healthy volunteers were immunized with either Hib PS conjugated to diphtheria toxoid (Hib PS-D) (Connaught Laboratories, Swiftwater, PA) or Hib oligosaccharide conjugated to Corynebacterium diphtheriae CRMI9' protein (Lederle Laboratories, Wayne, NJ).…”
Section: Methodsmentioning
confidence: 99%
“…However, two important subgroups of anti-Hib PS Ab have been identified. First, the immune response of most subjects immunized with Hib PS vaccine is quantitatively dominated by Ab expressing a cross-reactive idiotype, Hibid-1, which is associated with a VKII gene family member, A2 (2,4,6). We, and others have previously shown that these A2-encoded Ab appear to be unmutated, even if antigen is presented as a protein-conjugated polysaccharide (2,4).…”
mentioning
confidence: 99%
“…This idiotype seems to ensure optimal protection against Hib disease [20]. However, natural exposure in contrast to immunization may selectively stimulate Id-1 ÿ B cell clones [21]. It was also suggested that antibodies to Hib CP cross-reactive with E. coli K100 CP do not express Id-1 since they have either V , V I, or V III chains, but not V II [22].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, each individual antibody of older children and adults is encoded by a single V,II appears to generate anticarbohydrate antibodies from a limited gene, A2, and at least a portion of these antibodies are encoded number of B cell clones and, in contrast to antibody directed in an unmutated form, irrespective of antigen presentation as against protein antigens, these antibodies are not characterized plain polysaccharide or polysaccharide-protein conjugate form by extensive somatic hypermutation (7,8,87). Programmed (8,89,96). The majority of X anti-Hib polysaccharide antibody changes in variable region gene use and other diversifiers de-cross-reacts with the structurally related antigen Escherichia coli scribed above may explain the age-related acquisition of specific KlOO polysaccharide, and gastrointestinal colonization with this immunity.…”
Section: Developmentally Restricted Ig Gene Diversificationmentioning
confidence: 99%
“…Polysaccharideprotein conjugate Hib vaccines are capable of eliciting antibody in children as young as 2 mo of age. These infants appear to use the V,II gene segment encoding the predominant K light chains identified in older subjects (96). Whether these antibodies are produced by an alternative B cell subset or whether B cells specific for Hib polysaccharide are relatively less responsive to plain polysaccharide antigen compared to T-dependent antigen formulations in early development is the subject of ongoing investigation.…”
Section: Developmentally Restricted Ig Gene Diversificationmentioning
confidence: 99%